Soil pedotransfer functions for 4 mexican soils - Bell, M.A.; van Keulen, H. (Wiley, 1995)
Simulation models for design and testing of different land use management options require detailed soil data inputs, which are often not available. Under such circumstances, pedotransfer functions (PTF) can be used to predict soil properties such as cation‐exchange capacity (CEC) and moisture retention. We developed PTF for CEC and moisture retention at −1500 kPa for soils from four contrasting agro‐ecological environments in Mexico. The PTF relating CEC to clay content, soil organic matter content (SOM), and pH explained 96% of the variability. Analysis of the residuals showed the effects of clay at three sites and SOM at all sites to be similar, despite quite distinct agro‐ecological conditions and a wide range of SOM levels (8.0–40.0 g kg−1). The PTF, using SOM, clay, and pH, explained 93% of the variability across the four sites in moisture retention at −1500 kPa, and residuals showed similar behavior across the sites for both SOM and clay. Additionally, PTF from the literature for CEC and moisture retention at −1500 kPa were tested for the study data and adequate fits were found. Apart from PTF prediction, confidence in model output depends in part on the variability of soil properties at a site. Despite considerable absolute variation in soil properties among sites, the relative variability (i.e., coefficient of variation [CV]) across sites was quite similar, with electrical conductivity and micronutrient concentrations showing the highest CV, and pH, −1500 kPa soil moisture retention, and CEC the lowest; the latter results provided some degree of confidence in the application of PTF. The SOM content was strongly related to altitude and to silt + clay content.